Does the pattern of lymphatic drainage influence the risk of nodal recurrence in trunk melanoma patients with negative sentinel lymph node biopsy? - Morgado, Francisca Jácome (2021)
Background: There are conflicting data regarding the prognostic value of the lymphatic basin drainage pattern in melanoma patients and the evidence is scant in the setting of negative sentinel lymph node biopsy. Objective: To investigate whether the pattern of lymphatic basin drainage influences the risk of nodal disease in patients with melanoma of the trunk and negative sentinel lymph node biopsy. Methods: A case series of patients with trunk melanoma and negative sentinel lymph node biopsy was retrospectively evaluated. Clinicopathological features, the pattern of lymphatic drainage and nodal, metastatic, and overall recurrence-free survival were reviewed. Results: Of the 135 patients included, multiple lymphatic basin drainage was identified in 61 (45.2%). Ten of the 74 (13.5%) patients with single drainage developed nodal recurrence, compared with 2 of the 61 (3.6%) patients with multiple drainages (p = 0.04). Nodal recurrence-free survival was significantly longer in the group with multiple drainages than in the group with single drainage (175.6 vs. 138.7 months; p = 0.04). In multivariate analysis, single drainage was associated with a higher risk of nodal recurrence (HR = 4.54; p = 0.05). No significant differences in metastatic and overall recurrence-free survival were found between groups. Study limitations: Retrospective analysis, single-center study, small sample, detailed histopathologic information not always present. Conclusions: In patients with trunk melanoma and negative sentinel lymph node biopsy, multi-ple lymphatic basin drainage may be an independent risk factor for nodal disease recurrence.This factor may help to identify patients with negative sentinel lymph node biopsy with a higherrisk of nodal recurrence.